Rancang Bangun Sistem Keamanan Loker Menggunakan RFID Berbasis Arduino Uno Pada Loker Karyawan SMK Yadika 2 Jakarta - Andy Candra; Farida Nurlaila (CV. Multi Kreasi Media, 2022)
Technology is present as part of the complement and needs of human life, including in the field of locker security. Lockers are used to store valuable and important items, especially at work. Therefore, the locker requires high security. Users often forget and lose keys, and do not guarantee the safety of the items in the locker because theft can occur easily using various tools or other fake keys. There is solution using an Arduino Uno-based RFID. The research method used is observation, interviews and literature study. The results of the implementation and testing, this system can work well as planned. The questionnaire show that 88% of respondents agree and state that this system is appropriate if used in the workplace. The way this tool works is to open a locker by attaching an RFID card that has been registered according to the locker provided. In addition, the LED light can be an automatic signal. Where when the locker is open or not completely closed, the LED light will turn on, and when the locker is closed the LED light does not turn on. This system also features an application on android as a remote locker controller. It is hoped that locker security will be more guaranteed.